Creating Shared Value Through Service-Learning in Management Education. (October 2017) - Nikolova, Natalia; Andersen, Lisa
Service-learning has gained strong interest among educators as a model of experiential education through community engagement. Its potential to contribute to multiple stakeholders, including students, community partners, faculty, and university, is well recognized. While research has focused on elements of this teaching model that contribute to the realization of student-related benefits, there has been less emphasis on what aspects enable the creation of shared value to other stakeholders. We describe a postgraduate, elective management consulting course based on service-learning pedagogy, which has been running for 10 years at the University of Technology Sydney Business School leading to the completion of 75 community projects to date, and evaluate how it creates shared value to multiple stakeholders. We identify four main elements of the course that enable it to deliver value to multiple stakeholders: a dedicated role of client engagement coordinator, a coaching program involving industry experts, student autonomy, and authentic assessments. The main challenges in continuously providing value to all involved parties are developing focused and realistic project briefs, managing students' commitment and differences in students' skills, and recruiting industry coaches.